Curable silicone composition and cured product thereof, laminate, and optical device or optical display
By using specific types of organopolysiloxane and platinum group catalysts in curable silicone compositions, the problem of poor curing of UV delayed curable compositions on difficult-to-adhesive substrates is solved, and high bond strength and optical stability is achieved, and it is suitable for applications such as optical displays and touch panels.
Patent Information
- Application Number
- CN202380062635.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-12
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the ultraviolet delay curable silicone composition has poor curing in the part that is impermeable to ultraviolet rays, and the bonding strength to a substrate with difficult adhesiveness such as a polarizing plate with hard coating layer is reduced, and it is prone to yellowing under high temperature conditions, affecting optical stability.
The curable silicone composition of an alkenyl group containing an alkenyl group, an organopolysiloxane with a silicon atom bonded to a hydrogen atom, and a photoactivated platinum group metal catalyst with a wavelength of 200 to 500 nm is used to achieve ultraviolet delayed curability and high bonding strength by adjusting the component ratio and catalyst content, and maintaining optical stability under high temperature conditions.
It achieves high bonding strength to glass and substrates such as polarizers with hard coating, and has less yellowing at high temperatures, maintains optical stability, and is suitable for applications such as optical displays and touch panels.
Smart Images

Figure BDA0005289457490000201 
Figure BDA0005289457490000211 
Figure BDA0005289457490000212
Abstract
Description
Technical Field
[0001] The present invention relates to a curable silicone composition and a cured product thereof, a laminate, and an optical device or an optical display. Background Art
[0002] As an adhesive or pressure-sensitive adhesive for improving the visual confirmation of an optical display, a curable silicone composition with high transparency and large elongation of the cured product is used. Optical displays require the use of display parts such as liquid crystals and organic EL, touch panels, and display forming components such as cover glasses (cover lenses) that are unstable to heat, so the curable silicone composition used needs to be
[0003] Compositions that cure at relatively low temperatures. In recent years, compositions that cure by ultraviolet irradiation without requiring a heating step have attracted attention from the viewpoint of energy saving.
[0004] However, there are many cases where decorative parts are set on the periphery of the display. In the case of ultraviolet curable compositions, there is a problem of poor curing of the parts that are not transparent to ultraviolet rays. As a solution, there are low-temperature or room-temperature curable silicone compositions that do not require ultraviolet irradiation. For example, Document 1 proposes a curable silicone composition composed of a polysiloxane containing alkenyl groups, an organopolysiloxane containing silicon-bonded hydrogen atoms, an organic compound having an alkoxysilyl group, and a platinum-based catalyst. However, in low-temperature or room-temperature curable silicone compositions, curing is carried out while mixing, so there are limitations on the process. In addition, there is a problem that the washing of the device with residual mixed liquid becomes complicated.
[0005] Therefore, an ultraviolet delayed curing composition using a catalyst activated by ultraviolet irradiation is proposed. In the case of an ultraviolet delayed curing composition, the part that is not transparent to ultraviolet rays also has the characteristic of being cured after the catalyst is activated. It remains liquid and stable until ultraviolet rays are irradiated. For example, in Document 2, an ultraviolet curing silicone rubber composition composed of a polyorganosiloxane containing alkenyl groups, an organopolysiloxane containing silicon-bonded hydrogen atoms, and a platinum group metal catalyst activated by light of a wavelength of 200 to 500 nm is proposed. However, in order to cure it only with ultraviolet rays, a relatively large amount of platinum catalyst is required. A large amount of platinum catalyst may cause yellowing over time, and is not preferred as an adhesive for the display part of an optical display. Hereinafter, a composition containing a platinum catalyst activated by such ultraviolet rays will be referred to as an ultraviolet delayed curing composition.
[0006] On the other hand, the conventional ultraviolet delayed curing composition has the problem of poor adhesion from the hard coating on the polarizing plate used as an optical component. That is, unlike the substrates with relatively easy adhesion such as glass, there are many cases where a hard coating such as acrylic resin is provided on the polarizing plate, but if the ultraviolet delayed curing composition is used for such a polarizing plate, it is sometimes easy to cause poor curing after ultraviolet irradiation, and the bonding strength of the polarizing plate is greatly reduced. Therefore, in particular, as an OCR and an adhesive layer used for optical displays, it is strongly required that the ultraviolet delayed curing composition that can achieve sufficient adhesion is also achieved not only for glass, but also for polarizing plates provided with hard coatings.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Patent Publication No. 2020 / 080348 Pamphlet
[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-218495 Summary of the invention
[0011] Problems to be solved by the invention
[0012] Therefore, curable silicone compositions used in adhesives or adhesives for optical displays, touch panels, etc. are required to have excellent optical properties and delayed UV curing properties, and to exhibit excellent bonding strength even to substrates that are difficult to bond to, such as polarizing plates with hard coatings. Furthermore, regarding its optical properties, it is required to have a composition with excellent optical stability with little yellowing even when exposed to high temperature after curing.
[0013] The present invention is made to solve the above-mentioned prior art problems, and its purpose is to provide a curable silicone composition and its cured product, a laminate, and an optical device or an optical display that show excellent performance when used as a component requiring transparency such as an optical display or a touch panel. Specifically, the purpose of the present invention is to provide a curable silicone composition and its cured product, especially a laminate, an optical device, an optical display, etc. containing the cured product. The curable silicone composition is ultraviolet delayed curing, and can show a high adhesive strength as high as glass, etc., even for a substrate such as a polarizing plate with a hard coating on the surface, which shows a decrease in adhesive strength or poor adhesion due to hindered curing after ultraviolet irradiation, and the degree of yellowing is small even under high temperature conditions.
[0014] Solutions for solving problems
[0015] The present inventors have conducted in-depth research on the above-mentioned problems and have achieved the present invention. That is, the purpose of the present invention is achieved by a curable silicone composition, which comprises:
[0016] (A) an organopolysiloxane having at least two alkenyl groups having 2 to 12 carbon atoms in one molecule;
[0017] (B) the following components (b1) and (b2):
[0018] (b1) a linear organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the molecular chain ends,
[0019] (b2) an organohydrogenpolysiloxane having at least three silicon-bonded hydrogen atoms in one molecule;
[0020] (C) at least one selected from the following components (c1) and (c2):
[0021] (c1) an organic compound having two or more alkoxysilyl groups in one molecule,
[0022] (c2) an organic compound having an alkoxysilyl group and an epoxy group in one molecule; and
[0023] (D) a platinum group metal catalyst activated by light with a wavelength of 200 to 500 nm,
[0024] in,
[0025] The content of the component (B) is an amount in which the silicon-bonded hydrogen atoms in the component (B) account for 1 mol or more, relative to 1 mol of the aliphatic unsaturated carbon-carbon bonds in the component (A).
[0026] The content of platinum atoms in the component (D) is in a range of 15 ppm or less relative to the sum of components that form nonvolatile solid components by the curing reaction of the curable silicone composition.
[0027] The content of the component (C) is preferably in the range of 0.01 to 5% by mass based on the total amount of the curable silicone composition.
[0028] The component (b1) is preferably used together with the component (b2) in an amount of 60% by mass or more, and preferably in a range of 60 to 99% by mass, based on the sum of the components (b1) and (b2).
[0029] The component (A) is the following component (a1), and may contain component (a2):
[0030] (a1) a linear or partially branched organopolysiloxane having at least two alkenyl groups having 2 to 12 carbon atoms in one molecule
[0031] (a2) From the average unit formula: (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 SiO 3 / 2 ) c (SiO 4 / 2 ) d (Where R 1 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, R 1 An organopolysiloxane having an alkenyl group, wherein at least 1 mol % of the alkenyl group is an alkenyl group having 2 to 12 carbon atoms, and a, b, c and d satisfy all of the following conditions: a+b+c+d=1, 0≤a≤0.8, 0≤b≤0.4, 0≤c≤0.8, 0≤d≤0.6, 0.2≤c+d≤0.8)
[0032] (B) component is the following (b1) component and (b2) component:
[0033] (b1) a linear organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the molecular chain ends
[0034] (b2) an organohydrogenpolysiloxane having at least three silicon-bonded hydrogen atoms in one molecule, particularly preferably
[0035] Average unit formula: (R 2 3SiO 1 / 2 ) e (R 2 2SiO 2 / 2 ) f (R 2 SiO 3 / 2 ) g (SiO 4 / 2 ) h (Where R 2 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms other than an alkenyl group or a hydrogen atom, R 2 At least 1 mol % of which are hydrogen atoms, and e, f, g and h satisfy all of the following conditions: e+f+g+h=1, 0≤e≤0.8, 0≤f≤0.4, 0≤g≤0.7, 0≤h≤0.5, 0.2≤g+h≤0.7)
[0036] The viscosity of the composition before ultraviolet irradiation at 25° C. is preferably 100,000 mPa or less.
[0037] The curable silicone composition of the present invention is preferably an optical adhesive or an optical pressure-sensitive adhesive.
[0038] The content of the component (B) is preferably an amount in which the silicon-bonded hydrogen atoms in the component (B) are 1 mol or more and 4 mol or less per mol of the aliphatic unsaturated carbon-carbon bonds in the component (A).
[0039] The present invention also relates to a cured product of the curable silicone composition of the present invention.
[0040] The cured product of the curable silicone composition of the present invention preferably has a needle penetration at 25°C in the range of 5 to 70.
[0041] In addition, the present invention also relates to a laminated body,
[0042] It comprises an adhesive layer composed of the cured product of the present invention disposed between a first transparent or opaque optical member and a second transparent or opaque optical member.
[0043] Furthermore, the present invention also relates to an optical device comprising: a substrate; an optical element disposed on the substrate; and the cured product of the present invention, which seals at least a portion of the optical element.
[0044] Furthermore, the present invention also relates to an optical display including the laminated body of the present invention.
[0045] Effects of the Invention
[0046] The UV-curable silicone composition of the present invention has high transparency after curing and excellent bonding strength to glass and polarizing plates that are difficult to bond, so it is useful when used as an adhesive or pressure-sensitive adhesive for optical displays or touch panels. In addition, since the degree of yellowing is small even under high temperature conditions, an optical device or optical display with excellent optical stability over time can be provided. DETAILED DESCRIPTION
[0047] [Curable silicone composition]
[0048] First, the ultraviolet curable silicone composition of the present invention (hereinafter, sometimes referred to as “the present composition”) will be described in detail below.
[0049] The component (A) is an organopolysiloxane having in one molecule at least two alkenyl groups having a carbon number of 2 to 12. Examples of the alkenyl group in the component (A) include vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, undecenyl and dodecenyl. In view of economic efficiency and reactivity, vinyl, allyl, hexenyl and octenyl are preferred.
[0050] In addition, as other groups bonded to silicon atoms in component (A), there can be exemplified: alkyl groups having 1 to 12 carbon atoms such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl and dodecyl; aralkyl groups having 7 to 12 carbon atoms such as benzyl and phenethyl; alkyl groups having 1 to 12 carbon atoms substituted by halogen such as 3-chloropropyl and 3,3,3-trifluoropropyl, aryl groups having 6 to 20 carbon atoms such as phenyl, tolyl and xylyl; and groups in which a part or all of the hydrogen atoms of these groups are substituted by halogen atoms such as fluorine atoms, chlorine atoms and bromine atoms. Methyl groups are preferred from the perspective of economic efficiency and heat resistance. Furthermore, the silicon atoms in component (A) may be bonded with a small amount of alkoxy groups such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy and tert-butoxy, and hydroxyl groups within the range not impairing the purpose of the present invention.
[0051] The molecular structure of the component (A) is not limited, and examples thereof include linear, partially branched linear, branched, cyclic, or three-dimensional network structures. The component (A) may be a single organopolysiloxane having these molecular structures, or a mixture of two or more organopolysiloxanes having these molecular structures.
[0052] Preferably, the component (A) is the following component (a1), and may contain a component (a2):
[0053] (a1) a linear or partially branched organopolysiloxane having at least two alkenyl groups having 2 to 12 carbon atoms in one molecule
[0054] (a2) From the average unit formula: (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 SiO 3 / 2 ) c (SiO 4 / 2 ) d (Where R 1 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, R 1 An organopolysiloxane having an alkenyl group, wherein at least 1 mol % is an alkenyl group having 2 to 12 carbon atoms, and a, b, c and d satisfy all of the following conditions: a+b+c+d=1, 0≤a≤0.8, 0≤b≤0.4, 0≤c≤0.8, 0≤d≤0.6, 0.2≤c+d≤0.8).
[0055] Examples of the component (a1) include dimethyl polysiloxanes terminated at both ends of the molecular chain by dimethylvinyl siloxane groups, dimethyl polysiloxanes terminated at both ends of the molecular chain by diphenylvinyl siloxane groups, dimethyl siloxane / methyl phenyl siloxane copolymers terminated at both ends of the molecular chain by dimethylvinyl siloxane groups, dimethyl siloxane / diphenyl siloxane copolymers terminated at both ends of the molecular chain by diphenylvinyl siloxane groups, dimethyl siloxane / methyl phenyl siloxane copolymers terminated at both ends of the molecular chain by dimethylvinyl siloxane groups, dimethyl siloxane / methyl vinyl siloxane copolymers terminated at both ends of the molecular chain by dimethylvinyl siloxane groups, and dimethyl siloxane / methyl phenyl siloxane / methyl vinyl siloxane copolymers terminated at both ends of the molecular chain by dimethylvinyl siloxane groups. Siloxane-terminated dimethylsiloxane / diphenylsiloxane / methylvinylsiloxane copolymer, methylvinyl polysiloxane terminated at both ends of the molecular chain by trimethylsiloxane, methylvinyl siloxane / methylphenylsiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxane, methylvinyl siloxane / diphenylsiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxane, and dimethylsiloxane / methylvinyl siloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxane, partially branched molecular chain terminal dimethylvinylsiloxane terminated polydimethylsiloxane containing methylsilsesquioxane units (T units), molecular chain terminal dimethylvinylsiloxane terminated polydimethylsiloxane containing silicon dioxide units (Q units), and mixtures of two or more of these organopolysiloxanes.
[0056] In the component (a2), wherein R 1 Each independently represents a monovalent hydrocarbon group having 1 to 12 carbon atoms, and examples thereof include alkyl, alkenyl, aryl, aralkyl, and groups in which a part or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine. 1 At least 1 mol % of the total number of the alkenyl groups is an alkenyl group having 2 to 12 carbon atoms.
[0057] Examples of such component (a2) include tetrakis(dimethylvinylsiloxane)silane, hexa(dimethylvinylsiloxane)disiloxane, and an organopolysiloxane resin represented by the following average unit formula:
[0058] (ViMe2SiO 1 / 2 ) 0.1 (Me3SiO 1 / 2 ) 0.4 (SiO 4 / 2 ) 0.5
[0059] (ViMe2SiO 1 / 2 ) 0.1 (Me3SiO1 / 2 ) 0.5 (SiO 4 / 2 ) 0.4
[0060] (ViMe2SiO 1 / 2 ) 0.05 (Me3SiO 1 / 2 ) 0.55 (SiO 4 / 2 ) 0.4
[0061] (ViMe2SiO 1 / 2 ) 0.1 (Me3SiO 1 / 2 ) 0.4 (PhSiO 3 / 2 ) 0.1 (SiO 4 / 2 ) 0.4
[0062] (ViMe2SiO 1 / 2 ) 0.046 (Me3SiO 1 / 2 ) 0.394 (SiO 4 / 2 ) 0.56
[0063] (ViMe2SiO 1 / 2 ) 0.25 (PhSiO 3 / 2 ) 0.75 .
[0064] It should be noted that in the above formula, Me is a methyl group, Ph is a phenyl group, and Vi is a vinyl group.
[0065] The content of component (a2) is in the range of 0 to 10.0% by mass, preferably in the range of 0 to 5.0% by mass, relative to the solid content of the curable silicone composition. Here, the solid content refers to the sum of components that form non-volatile solid components through a curing reaction, and particularly includes components (A) to (D) constituting the present composition and any non-volatile components.
[0066] As the component (A), a linear or partially branched organopolysiloxane having at least two alkenyl groups with 2 to 12 carbon atoms in one molecule (a1) is particularly preferred, and a linear organopolysiloxane having alkenyl groups with 2 to 12 carbon atoms at both ends of the molecular chain (a1-1) is particularly preferred. Such a component (a) can provide elongation and flexibility to the obtained cured product and achieve excellent mechanical strength. In addition, a part of the component (A) may be the above-mentioned component (a2), and by having T units or Q units, the mechanical strength, especially hardness and toughness of the cured product may be improved. On the other hand, when the content of the component (a2) is high, the curing speed of the composition after ultraviolet irradiation may sometimes slow down. Therefore, from the viewpoint of maintaining a practical curing speed, the component (A) may be composed only of the component (a1) or the component (a1-1), and this is preferred. In order to satisfy the required properties such as hardness, by using the components (a1) and (a2) together as the component (A) at a mass ratio of 100:0 to 80:20, the mechanical strength of the obtained cured product can be improved while maintaining a practical curing speed.
[0067] The viscosity of the component (A) at 25°C (the overall viscosity in the case of a mixture) is not limited, but is preferably 100,000 mPa·s or less, within the range of 100 to 100,000 mPa·s, within the range of 100 to 50,000 mPa·s, or within the range of 100 to 10,000 mPa·s. This is because if the viscosity of the component (A), especially the component (a1), is above the lower limit of the above range, the mechanical properties of the obtained cured product are improved, and on the other hand, if it is below the upper limit of the above range, the workability of the obtained composition is improved.
[0068] The component (B) is an organopolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule. As groups bonded to silicon atoms other than silicon-bonded hydrogen atoms in the component (B), there can be exemplified: alkyl groups having 1 to 12 carbon atoms such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl; aryl groups having 6 to 20 carbon atoms such as phenyl, tolyl, and xylyl; arylalkyl groups having 7 to 20 carbon atoms such as benzyl and phenethyl; alkyl groups having 1 to 12 carbon atoms substituted with halogen such as 3-chloropropyl and 3,3,3-trifluoropropyl, preferably methyl and phenyl from the perspective of economy and heat resistance. Furthermore, the silicon atoms in the component (B) may also be bonded with a small amount of alkoxy groups and hydroxyl groups such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, and tert-butoxy, within the scope that does not impair the purpose of the present invention.
[0069] The component (B) consists of the following components (b1) and (b2):
[0070] (b1) a linear organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the molecular chain ends,
[0071] (b2) an organohydrogenpolysiloxane having at least three silicon-bonded hydrogen atoms in one molecule,
[0072] The component (b2) may be composed in particular of the following
[0073] Average unit formula: (R 2 3SiO 1 / 2 ) e (R 2 2SiO 2 / 2 ) f (R 2 SiO 3 / 2 ) g (SiO 4 / 2 ) h (Where R 2 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms other than an alkenyl group or a hydrogen atom, R 2 At least 1 mol % of which are hydrogen atoms, and e, f, g and h satisfy all of the following conditions: e+f+g+h=1, 0≤e≤0.8, 0≤f≤0.4, 0≤g≤0.7, 0≤h≤0.5, 0.2≤g+h≤0.7)
[0074] The component (B) of the present invention uses the component (b1) and the component (b2) together, but the amount of the component (b1) used is preferably 60% by mass or more, more preferably in the range of 60 to 99% by mass, and even more preferably in the range of 80 to 98% by mass relative to the sum of the components (b1) and (b2). That is, the main part of the component (B) is the component (b1) as a chain extender, and by using a small amount of the component (b2) together, the flexibility and mechanical strength of the cured reaction product, the adhesion to various substrates, etc. can be more effectively improved.
[0075] The component (b1) is a linear or partially branched organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain, and functions as a chain extender in the hydrosilylation reaction with the component (A) to improve the flexibility of the cured product.
[0076] As the component (b1), for example, 1,1,3,3-tetramethyldisiloxane, tri(dimethylhydrogensiloxane)methylsilane, bis(dimethylhydrogensiloxane)diphenylsilane, dimethylpolysiloxane having dimethylhydrogensiloxane groups blocking both ends of the molecular chain, branched polydimethylsiloxane having dimethylhydrogensiloxane groups blocking both ends of the molecular chain containing methylsilsesquioxane units (T units), branched polydimethylsiloxane having dimethylhydrogensiloxane groups blocking both ends of the molecular chain containing silicon dioxide units (Q units), and mixtures of two or more of these organopolysiloxanes can be exemplified. It should be noted that the component (b1) may have silicon-bonded hydrogen atoms in the side chain portion, but a linear organohydrogenpolysiloxane having only silicon-bonded hydrogen atoms at both ends of the molecular chain is particularly preferred. For the dimethylpolysiloxane having dimethylhydrogensiloxane groups blocking both ends of the molecular chain, a siloxane polymerization degree in the range of 2 to 100, particularly preferably in the range of 2 to 50, can be exemplified.
[0077] In the component (b2), in the above average unit formula, R 2 Each independently represents a monovalent hydrocarbon group having 1 to 12 carbon atoms or a hydrogen atom other than an alkenyl group, and examples thereof include an alkyl group, an aryl group, an aralkyl group, and groups in which a part or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine atoms, chlorine atoms, and bromine atoms. 2 At least 1 mol % of the carbon atoms are hydrogen atoms.
[0078] Examples of such component (b2) include tetrakis(dimethylhydrogensiloxane)silane, hexa(dimethylhydrogensiloxane)disiloxane, tris(dimethylhydrogensiloxane)phenylsilane, and an organopolysiloxane resin represented by the following average unit formula:
[0079] (HMe2SiO 1 / 2 ) 0.6 (SiO 4 / 2 ) 0.4
[0080] (HMe2SiO 1 / 2 ) 0.3 (Me3SiO 1 / 2 ) 0.3 (SiO 4 / 2 ) 0.4
[0081] (HMe2SiO 1 / 2 ) 0.5 (Me3SiO 1 / 2 ) 0.05 (SiO 4 / 2 ) 0.4
[0082] (HMe2SiO 1 / 2) 0.5 (PhSiO 3 / 2 ) 0.1 (SiO 4 / 2 ) 0.4
[0083] (HMe2SiO 1 / 2 ) 0.6 (PhSiO 3 / 2 ) 0.4
[0084] (HMe2SiO 1 / 2 ) 0.75 (PhSiO 3 / 2 ) 0.25 .
[0085] It should be noted that in the above formula, Me is a methyl group and Ph is a phenyl group.
[0086] The content of component (b2) is preferably in the range of 0.001 to 2.0% by mass, preferably in the range of 0.01 to 1.0% by mass, relative to the solid content of the curable silicone composition. Here, the solid content refers to the sum of components that form non-volatile solid components through a curing reaction, and particularly includes components (A) to (D) constituting the present composition and any non-volatile components.
[0087] The viscosity of the component (B) at 25°C (the overall viscosity of the mixture) is not limited, but is preferably 10,000 mPa·s or less, in the range of 1 to 1,000 mPa·s, or in the range of 1 to 500 mPa·s. This is because if the viscosity of the component (B) is at least the lower limit of the above range, the mechanical properties of the obtained cured product are improved, while on the other hand, if the viscosity of the component (B) is at most the upper limit of the above range, the transparency and workability of the obtained composition are improved.
[0088] Relative to 1 mole of aliphatic unsaturated carbon-carbon bonds in component (A), the content of component (B) is an amount of more than 1 mole of silicon-bonded hydrogen atoms in this component, preferably an amount of more than 1 mole and less than 4 moles, more preferably an amount in the range of 1 to 2 moles, an amount in the optional range of these upper and lower limits. This is because, if the content of component (B) is above the lower limit of the above range, the obtained composition, under the premise of being used together with the specific (C) component described later, will also exert sufficient practical adhesion even for substrates with poor adhesion such as polarizing plates with hard coatings. On the other hand, if it is below the upper limit of the above range, it has the advantage that the mechanical strength of the obtained cured product is easily improved. It should be noted that the ratio of the amount (moles) of silicon-bonded hydrogen atoms in component (B) relative to 1 mole of aliphatic unsaturated carbon-carbon bonds in component (A) is sometimes referred to as "SiH / Vi ratio" below.
[0089] In the present invention, by selecting the above-mentioned components (A), (B) and the component (C) having a specific structure described later, especially satisfying the specified range of SiH / Vi ratio, it is possible to effectively eliminate the problem of hindering curing and achieve excellent bonding strength even in substrates with poor adhesion such as polarizing plates with hard coatings. On the other hand, if the above-mentioned range of SiH / Vi ratio is not satisfied, or if component (C) is not used together, the bonding strength to polarizing plates with hard coatings is reduced, and sometimes the technical effect of the present invention cannot be achieved.
[0090] The component (C) is one or more selected from the group consisting of a compound having two or more alkoxysilyl groups in one molecule of (c1) and an organic compound having an alkoxysilyl group and an epoxy group in one molecule of (c2). The component (c1), the component (c2) or a mixture thereof may also be used. The component (C) acts as an adhesion promoter that improves the adhesion strength of the components (A), (B) and the present composition. Examples of the alkoxysilyl group include trimethoxysilyl, methyldimethoxysilyl, triethoxysilyl, methyldiethoxysilyl and triisopropoxysilyl.
[0091] Specifically, the component (C) may be (c1) an organic compound having two or more alkoxysilyl groups at the end of the molecular chain. In addition, the organic compound referred to herein includes, in addition to alkane compounds and the like, organosilicon compounds. Specific examples of the component (c1) include: 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, 1,2-bis(methyldimethoxysilyl)ethane, 1,2-bis(methyldiethoxysilyl)ethane, 1,3-bis(trimethoxysilyl)propane, 1,4-bis(trimethoxysilyl)butane, 1,4-bis(triethoxysilyl)butane, 1-methyldimethoxysilyl-4-trimethoxysilylbutane, 1-methyldiethoxysilyl-4-triethoxysilyl Alkyl butane, 1,4-bis(methyldimethoxysilyl)butane, 1,4-bis(methyldiethoxysilyl)butane, 1,5-bis(trimethoxysilyl)pentane, 1,5-bis(triethoxysilyl)pentane, 1,4-bis(trimethoxysilyl)pentane, 1,4-bis(triethoxysilyl)pentane, 1-methyldimethoxysilyl-5-trimethoxysilylpentane, 1-methyldiethoxysilyl-5-triethoxysilylpentane, 1,5-bis(methyldimethoxysilyl)pentane, 1,5-bis(methyl 1,6-bis(trimethoxysilyl)hexane, 1,6-bis(triethoxysilyl)hexane, 1,4-bis(trimethoxysilyl)hexane, 1,5-bis(trimethoxysilyl)hexane, 2,5-bis(trimethoxysilyl)hexane, 1-methyldimethoxysilyl-6-trimethoxysilylhexane, 1-phenyldiethoxysilyl-6-triethoxysilylhexane, 1,6-bis(methyldimethoxysilyl)hexane, 1,7-bis(trimethoxysilyl)heptane, 2,5-bis(trimethoxysilyl)hexane Alkane compounds having two alkoxysilyl groups such as (trimethoxysilyl)heptane, 2,6-bis(trimethoxysilyl)heptane, 1,8-bis(trimethoxysilyl)octane, 1,8-bis(methyldimethoxysilyl)octane, 2,5-bis(trimethoxysilyl)octane, 2,7-bis(trimethoxysilyl)octane, 1,9-bis(trimethoxysilyl)nonane, 2,7-bis(trimethoxysilyl)nonane, 1,10-bis(trimethoxysilyl)decane and 3,8-bis(trimethoxysilyl)decane;Disiloxane compounds having two alkoxysilyl groups such as 1,3-bis{2-(trimethoxysilyl)ethyl}-1,1,3,3-tetramethyldisiloxane, 1,3-bis{2-(methyldimethoxysilyl)ethyl}-1,1,3,3-tetramethyldisiloxane, 1,3-bis{2-(triethoxysilyl)ethyl}-1,1,3,3-tetramethyldisiloxane, 1,3-bis{2-(methyldiethoxysilyl)ethyl}-1,1,3,3-tetramethyldisiloxane, 1,3-bis{6-(trimethoxysilyl)hexyl}-1,1,3,3-tetramethyldisiloxane, and 1,3-bis{6-(triethoxysilyl)hexyl}-1,1,3,3-tetramethyldisiloxane. In addition, examples of organic compounds having three alkoxysilyl groups include trisiloxane compounds having three alkoxysilyl groups, such as 1,3,5-tris{2-(trimethoxysilyl)ethyl}-1,1,3,5,5-pentamethyltrisiloxane, 1,3,5-tris{2-(methyldimethoxysilyl)ethyl}-1,1,3,5,5-tetramethyldisiloxane, 1,3,5-tris{2-(triethoxysilyl)ethyl}-1,1,3,5,5-tetramethyldisiloxane, 1,3,5-tris{2-(methyldiethoxysilyl)ethyl}-1,1,3,5,5-tetramethyldisiloxane, and 1,3,5-tris{6-(trimethoxysilyl)hexyl}-1,1,3,5,5-tetramethyldisiloxane. An example of the structure thereof is the following formula:
[0092] (MeO)3SiCH2CH2(Me)2Si-O-SiMe(CH2CH2Si(OMe)3)-O-Si(Me)2CH2CH2Si(OMe)3
[0093] (In the above formula, Me is methyl).
[0094] Similarly, the component (C) may be a compound having an alkoxysilyl group and an epoxy group in one molecule of the component (c2). Specific examples of the component (c2) include: 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.
[0095] In order to achieve the technical effect of the present invention, it is essential that the type of component (C), the above-mentioned components (A) and (B) and their SiH / Vi meet the prescribed range. If only a tackifier is added, the adhesive force will be reduced due to the problem of poor curing in a substrate with a hard-coated polarizing plate or the like, and when a tackifier other than the above-mentioned component (C) is used, in addition to sometimes being unable to obtain sufficient adhesive force, sometimes the compatibility with components (A) and (B) is reduced, or the transparency of the obtained cured product is deteriorated, or yellowing occurs, and as an OCR or adhesive for optical components, practical performance cannot be achieved.
[0096] The content of the component (C) is not limited, but is preferably in the range of 0.01 to 5 parts by mass or in the range of 0.01 to 3 parts by mass relative to 100 parts by mass of the total of the components (A) to (D), from the viewpoint of not promoting the curing characteristics or discoloration of the cured product.
[0097] The component (D) is a catalyst for the hydrosilylation reaction for accelerating the curing of the present composition and is a platinum group metal catalyst activated by light having a wavelength of 200 to 500 nm.
[0098] The content of component (D) is an amount that promotes the curing of the present composition. Specifically, the platinum atoms in the catalyst are in an amount in the range of 0.1 to 15 ppm by mass relative to the present composition, preferably in the range of 5 to 15 ppm. This is because if the content of component (D) is above the lower limit of the above range, the curing of the obtained composition is fully carried out. On the other hand, if the content of component (D) is below the upper limit of the above range, the obtained cured product is not easy to color. On the other hand, if the amount of component (D) used exceeds the above upper limit, the obtained cured product is sometimes easy to color over time, resulting in yellowing problems, and practical performance cannot be achieved as an OCR or adhesive for optical components. That is, the present invention can solve the problem of poor curing in difficult-to-bond substrates such as polarizing plates with hard coatings not only by increasing the amount of the catalyst (component (D)), but also by using other components and a specified SiH / Vi ratio together.
[0099] The component (D) is a catalyst for hydrosilylation reaction which is inactive if not irradiated with high energy rays having a wavelength of 200 to 500 nm, but becomes active by irradiation with high energy rays. The component (D) is known in the art as a so-called ultraviolet-activated catalyst or a high energy ray-activated catalyst.
[0100] The amount of ultraviolet radiation varies depending on the type of ultraviolet-activated catalyst, but the cumulative radiation amount at a wavelength of 365 nm is preferably 100 mJ / cm 2 ~10J / cm2 within the range.
[0101] Specific examples of the component (D) include trimethyl(methylcyclopentadienyl)platinum(IV), (cyclopentadienyl)trimethylplatinum(IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum(IV), (cyclopentadienyl)dimethylethylplatinum(IV), (cyclopentadienyl)dimethylacetylplatinum(IV), (trimethylsilylcyclopentadienyl)trimethylplatinum(IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum(IV), (dimethylphenylsilylcyclopentadienyl)trimethylcyclopentadienylplatinum(IV), trimethyl(acetylacetylacetonate)platinum(IV), trimethyl(3,5-heptadienyl)trimethylplatinum(IV), and trimethyl(3,5-heptadienyl)trimethylplatinum(IV). bis(2,4-pentanedione)platinum(II), bis(2,4-hexanedione)platinum(II), bis(2,4-heptanedione)platinum(II), bis(3,5-heptanedione)platinum(II), bis(1-phenyl-1,3-butanedione)platinum(II), bis(1,3-diphenyl-1,3-propanedione)platinum(II), bis(hexafluoroacetylacetylacetonate)platinum(II), among which (methylcyclopentadienyl)trimethylplatinum(IV) and bis(2,4-pentanedione)platinum(II) are preferred from the aspects of versatility and ease of acquisition.
[0102] As the component (D), another catalyst for hydrosilylation reaction which exhibits activity without irradiation with ultraviolet rays may be optionally contained.
[0103] Furthermore, as long as the purpose of the present invention is not impaired, the present composition may contain metal oxide fine powders such as fumed silica and wet silica as needed; low molecular weight siloxanes containing alkenyl groups as reactive diluents such as 1,1,3,3-tetramethyl-1,3-divinyldisiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane; hindered phenol compounds such as 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-hydroxymethylphenol and 2,6-bis(hydroxymethyl)-p-cresol that act as storage stability improvers; and heat resistance improvers such as N-nitrosophenylhydroxylamine aluminum salt.
[0104] Preferably, the present composition may also contain a non-reactive organopolysiloxane as a plasticizer or viscosity modifier for the cured product. Specifically, examples may include a linear or branched organopolysiloxane or organopolysiloxane resin that does not contain functional groups such as alkenyl. Specifically, a polydimethylsiloxane having a trimethylsiloxy terminal is preferred. In particular, by using this component, the hardness (penetration) and fluidity (viscosity) in a cured state or a semi-cured state can be adjusted to a desired range.
[0105] The viscosity of the present composition at 25°C is not limited, but is preferably less than 100,000 mPa·s, within the range of 100 to 100,000 mPa·s, or within the range of 100 to 30,000 mPa·s. This is because if the viscosity of the present composition is above the lower limit of the above range, the mechanical properties of the obtained cured product are good, and on the other hand, if the viscosity of the present composition is below the upper limit of the above range, the operability of the obtained composition is good, and it is not easy to entrain air into the cured product. It should be noted that these viscosities can be measured by a rotational viscometer.
[0106] The present composition can be prepared by uniformly mixing the components (A) to (D) and any other components as required. When preparing the present composition, various stirrers or mixers can be used to mix at room temperature, or under heating as required. In addition, the order of mixing the components is not limited, and the components can be mixed in any order.
[0107] The present composition may be a one-component composition in which all components are prepared in the same container, or may be a two-component composition that is mixed before use in consideration of storage stability.
[0108] The present composition can be cured by ultraviolet irradiation with a wavelength of 200 to 500 nm. It should be noted that the curing reaction of the present composition can be adjusted to a desired speed by changing the concentration of the platinum catalyst in the component (D), the amount of ultraviolet irradiation, or the weight ratio of the component (A) to the component (B).
[0109] [Use of this composition]
[0110] This composition is useful as various potting agents, sealants, adhesives / adhesives, preferably as optical sealants, optical adhesives / adhesives, and in particular, as sealants and optical adhesives / adhesives for displays. This composition is cured by irradiation with high-energy rays such as ultraviolet rays even at low temperatures. Its cured product has large elongation, excellent flexibility and bonding strength, less coloring (yellowing) at high temperatures, and is not prone to turbidity. Therefore, it is preferably used as a material for forming an intermediate layer between the image display portion and the protective portion of a display. Such usage is sometimes referred to as an optical elastic resin ("OCR (Optically Clear Resin)"). In addition, since curing is performed even without a heating process, the process from bonding between components to curing / bonding by ultraviolet irradiation can be shortened without an additional heating process, which is suitable for energy-saving processes and can improve industrial production efficiency.
[0111] The present composition is not limited to liquid crystal displays, and can be used in the entire display field, such as organic EL displays, electronic paper displays, plasma displays, etc.
[0112] The composition can be cured without a heating step, and thus can be applied to substrates that lack heat resistance. Such substrates are usually transparent substrates such as glass, synthetic resin films / sheets, and transparent electrode coatings.
[0113] There is no particular limitation on the coating method of the present composition, and examples thereof include dispensing, gravure coating, micro gravure coating, slit coating, slot die coating, screen printing, template printing, and comma coating. It should be noted that, in the case where the present composition is used as an OCR for the bonding between components such as an optical display, a resin component, a so-called dam filling glue material (Dual Adhesive Material) can be optionally formed in a frame shape on the display module, or the present composition can be applied to its inner side in a manner without a dam filling glue, and the front panel is bonded therefrom. In addition, it can be that, according to the injection or configuration position, a dispensing machine such as a syringe or a cartridge is used to inject the curable silicone composition involved in the present invention and fill it, and configure the OCR. These processes can be carried out in the same manner as the configuration or injection process of the OCR disclosed in, for example, patent document 1 (International Patent Publication WO2020 / 080348 Pamphlet), and are preferably.
[0114] The composition of the present invention can be cured by irradiating ultraviolet rays. As the ultraviolet light source, a high-pressure mercury lamp, a medium-pressure mercury lamp, a Xe-Hg lamp, a deep UV lamp, a UV-LED light source, etc. are preferred, and ultraviolet light irradiation with a wavelength of 280 to 405 nm, preferably a wavelength of 300 to 405 nm, is particularly preferred. A light source with multiple luminous bands can also be used. Further, when the composition of the present invention is cured, the configured composition can be directly irradiated with ultraviolet rays, or ultraviolet rays can be irradiated through a light-transmitting component, and ultraviolet rays can also be irradiated from the gap between the components to cure the deep part. The irradiation method can be appropriately selected according to the bonding and curing process.
[0115] The amount of ultraviolet light used to cure the composition of the present invention can be appropriately designed according to the coating amount, coating thickness, curing process, desired cycle time, etc., but the cumulative light amount is 100 mJ / cm 2 ~20,000mJ / cm 2 , more preferably 1,000 mJ / cm 2 ~15,000mJ / cm 2 , more preferably 2,000 mJ / cm 2 ~10,000mJ / cm 2.
[0116] [cured material]
[0117] The cured product of the present invention (hereinafter, sometimes referred to as "the present cured product") is characterized by being obtained by curing the above-mentioned ultraviolet delayed-curing silicone composition.
[0118] As described above, the present composition is preferably used as a protective, sealing, bonding / adhesive
[0119] The optical elastic resin ("OCR (Optically Clear Resin)") is preferably cured to form an elastomer resin member or a gel-like resin member. For the cured silicone resin member, the needle penetration specified by JIS K2220 at 25°C (hereinafter referred to as "needle penetration") is preferably in the range of 5 to 70, and the needle penetration is more preferably in the range of 10 to 60, and in the range of 10 to 50. Such a cured product (=silicone resin member) has moderate softness and durability, and is excellent in adhesion / closedness retention and followability between components. Therefore, by using it as a gap sealant composition for a display device, a reliable gap shielding effect can be achieved.
[0120] As a method for forming the present cured product, for example, after applying the present composition on a film-like substrate, a tape-like substrate or a sheet-like substrate, it can be cured by irradiating ultraviolet rays (preferably using the above-mentioned light source and irradiation amount). In addition, it can be listed that: the present composition is first arranged between two substrates for curing, and the two substrates are firmly bonded, and the present composition is smoothly applied to at least one surface of the above-mentioned substrate, the two substrates are attached, and the two substrates are cured by irradiation with ultraviolet rays, and the situation of firmly bonding. The film thickness of the cured product is not limited, preferably 1 to 100,000 μm, more preferably 50 to 30,000 μm. It should be noted that, when the present cured product is formed between components, as described above, a resin component, a so-called dam filling glue material, can be optionally formed in a frame shape in the display module, or the present composition can be arranged on the inner side thereof in a manner without dam filling glue, and the front panel is attached thereto, and it is cured by irradiating ultraviolet rays from the side that can irradiate ultraviolet light, and it is preferred. Such a formation process of the cured product can be performed similarly to the curing process after the arrangement or injection of the OCR disclosed in, for example, Patent Document 1 (International Patent Publication No. WO2020 / 080348), and is preferably performed.
[0121] [Laminated body]
[0122] The laminate involved in the present invention is characterized in that it has: a first optical component, a second optical component, and an adhesive layer composed of the present cured product disposed between the two optical components. Here, these optical components may be transparent or opaque, or one or both may be transparent according to the target structure and the ultraviolet irradiation process. As such a laminate, it is preferred that the optical components and the formation process of the laminate used therein are common, for example, with the laminate disclosed in Patent Document 1 (International Patent Publication WO2020 / 080348 Pamphlet), and the composition used in the laminate disclosed in Patent Document 1 and part or all of its cured product can be replaced with the composition of the present invention or the present cured product for use, and can be used as a reference for the preferred embodiment of the present invention. In this case, it goes without saying that the curing of the composition in Patent Document 1 should be replaced, or the curing should be performed together with the curing by ultraviolet irradiation of the composition in the present invention.
[0123] [Optical device]
[0124] The optical device involved in the present invention (hereinafter sometimes referred to as "the present optical device") comprises: a substrate; an optical element, arranged on the substrate; and the present cured product, which seals at least a portion of the optical element, and the present optical device is preferably an optical semiconductor device. As the present optical device and its structure, it is preferred that, for example, it is common with the optical device disclosed in Patent Document 1 (International Patent Publication No. WO2020 / 080348 Pamphlet), and a part or all of the composition used in the various optical devices disclosed in Patent Document 1 and its cured product can be replaced with the composition of the present invention or the present cured product for use, and can be used as a reference for a preferred embodiment of the present invention.
[0125] [Optical Display]
[0126] The optical display involved in the present invention (hereinafter, sometimes referred to as "the present optical display") has the above-mentioned laminate, preferably further has one or more image display panels, and in addition, may have one or more touch panels. As a preferred type and structure of the present optical display, for example, it is common with the optical display disclosed in Patent Document 1 (International Patent Publication WO2020 / 080348 Pamphlet), and the composition used for various optical displays disclosed in Patent Document 1 and part or all of the cured product thereof can be replaced with the composition of the present invention or the cured product for use, and can be used as a reference for a preferred embodiment of the present invention.
[0127] Industrial Applicability
[0128] The curable silicone composition of the present invention and its cured product have high transparency and excellent bonding strength, so they can be preferably used for optical displays and touch panels. In addition, since no reaction is performed before irradiation with ultraviolet rays, and the part that is not directly irradiated with ultraviolet rays also reacts more delayed than the part that is directly irradiated, it can be applied to various processes. After curing, in addition to glass, sufficient adhesion is also shown to substrates such as polarizing plates, so it is useful as an adhesive and adhesive used in display devices such as optical displays (including touch panels) and optical semiconductor devices (including Micro LEDs). In addition, the composition of the present invention, in addition to the polarizing plates coated on the surface, can also be expected to exert the same effect on substrates such as acrylic acid as a raw material close to its surface coating material. Further, the cured product involved in the present invention has excellent transparency in addition to heat resistance, cold resistance and excellent bonding strength, especially less yellowing even under high temperature conditions, so it is extremely useful as an OCR layer or optical adhesive layer used in display devices such as displays (especially including vehicle-mounted displays, displays of aircraft with curved surfaces, etc., but not limited to this).
[0129] Example
[0130] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to the examples. In addition, the measurements and evaluations in the examples were performed as described below. It should be noted that the obtained cured product was visually confirmed to be transparent.
[0131] [Viscosity of composition]
[0132] The UV delayed curing silicone composition was placed in a rheometer (MCR301 manufactured by Anton Paar) using a cone and plate fixture with a diameter of 25 mm and set with a gap of 0.05 mm. The viscosity of the composition before UV irradiation was measured at a shear rate of d(gamma) / dt=10 / s.
[0133] [Needle penetration of cured product]
[0134] A curable silicone composition having a thickness of 10 mm or more was filled in a petri dish, and a UV-LED ultraviolet irradiation device (manufactured by JATEC) was used to irradiate the mixture at 1300 mW / cm 2 Irradiation 4,000mJ / cm 2 After being exposed to ultraviolet rays of 365 nm in wavelength, the mixture was placed in an oven at 90°C for 30 minutes for curing, and then cooled to 25°C, and the penetration at 25°C was measured using a penetration meter (RPM-201 manufactured by Rigo Corporation).
[0135] [Curing behavior of the composition]
[0136] The ultraviolet delayed curing silicone composition was placed in a rheometer (MCR302 manufactured by Anton Paar) and a parallel plate fixture with a diameter of 15 mm was used. The plate was set with a gap of 0.1 mm and then a UV light source device (REX-250 manufactured by Asahi Spectroscopy Corporation) was used to generate a UV light at a power of about 90 mW / cm 2 Irradiate ultraviolet light with a wavelength of 365nm to 4000mJ / cm 2 , confirm the curing behavior. The gel time defined below was determined.
[0137] Gel time: The time from the start of light irradiation when the loss tangent (tanδ) at 25°C reaches 1
[0138] [Shear bond strength and elongation of cured product to glass / glass]
[0139] The size of the cured silicone composition is 200 mm 2 A 200 μm-thick ultraviolet curable silicone composition was filled between two glass plates (Partech float glass, length 75 mm × width 25 mm × thickness 2 mm) and a UV-LED ultraviolet irradiation device (manufactured by JATEC) was used at 1300 mW / cm 2 Irradiate with ultraviolet light of wavelength 365nm to 4,000mJ / cm 2 , a test body consisting of a cured product sandwiched between two glass plates was prepared. A shear bonding test was performed on the test body in accordance with the method specified in JIS K6850, and the shear bonding strength of the cured product was measured. At the same time, the ratio of the deformation amount at break to the thickness of the cured product was recorded as elongation (%). The initial value determination was carried out three days after the test body was prepared. It should be noted that when evaluating the bonding strength and elongation, the measurement results of the tensile speed of 100 mm / min for each test body were used.
[0140] [Shear bond strength and elongation of cured product to polarizing plate / glass]
[0141] A polarizing plate with an adhesive layer (manufactured by Sanritz, with a hard coat layer) was attached to one side of a glass plate (75 mm long × 25 mm wide × 2 mm thick), and the size of the cured silicone material after curing was 200 mm between the polarizing plate and the other glass plate. 2 The ultraviolet curable silicone composition was filled in a manner to a thickness of 200 μm, and a UV-LED ultraviolet irradiation device (manufactured by JATEC) was used at 1300 mW / cm 2 Irradiate the glass surface with ultraviolet light of wavelength 365nm to 4,000mJ / cm 2, a test body consisting of a cured product clamped between glass and a polarizing plate was prepared. A shear bonding test was performed on the test body according to the method specified in JIS K6850, and the shear bonding strength of the cured product was measured. At the same time, the ratio of the deformation amount at break to the thickness of the cured product was recorded as elongation (%). The initial value determination was carried out three days after the test body was prepared. It should be noted that when evaluating the bonding strength and elongation, the measurement results of the tensile speed of 100 mm / min for each test body were used.
[0142] [Comparison of shear bond strength]
[0143] The shear bonding strength to glass and the shear bonding strength to the polarizing plate are compared by the following formula.
[0144] (shear bond strength of polarizing plate / glass) / (shear bond strength of glass / glass)×100[yellowness of cured product]
[0145] A UV-LED ultraviolet irradiation device (manufactured by JATEC) was used to irradiate a test body filled with a curable silicone composition between two glass plates (75 mm long × 50 mm wide × 2 mm thick, Corning Eagle XG) so that the size of the cured silicone composition was 35 mm long × 35 mm wide × 1.5 mm thick. The test body was irradiated at 1300 mW / cm 2 Irradiate with ultraviolet light of wavelength 365nm to 4,000mJ / cm 2 , and placed in an oven at 100°C for 500 hours. Then, taken out of the oven, and the yellowness index YI (E313-96) was measured using CM-5 (manufactured by Konica Minolta). [Examples 1 to 5, Comparative Examples 1 to 4]
[0146] Using the following components, curable silicone compositions having the compositions (parts by mass) shown in Table 1 were prepared. In each structural formula, Me is a methyl group, and Vi is a vinyl group.
[0147] As (A) component, the following components were used.
[0148] a1-1: ViMe2SiO(SiMe2O) 150 OSiMe2Vi
[0149] a1-2: ViMe2SiO(SiMe2O) 300 OSiMe2Vi
[0150] a1-3: ViMe2SiO(SiMe2O) 500 OSiMe2Vi
[0151] a1-4: ViMe2SiO(SiMe2O) 900OSiMe2Vi
[0152] a1-5: ViMe2SiO(SiMe2O) 60 OSiMe2Vi
[0153] As (B) component, the following components were used.
[0154] b1-1: HMe2SiO(SiMe2O) 24 OSiMe2H
[0155] b2-1: (HMe2SiO 1 / 2 ) 0.63 (SiO 4 / 2 ) 0.37
[0156] As (C)component, the following components were used.
[0157] c1-1: 1,6-bis(trimethoxysilyl)hexane
[0158] c2-1: Glycidoxypropyltrimethoxysilane
[0159] As (D)component, the following components were used.
[0160] d1-1: Trimethyl(methylcyclopentadienyl)platinum(IV)
[0161] As other optional components, the following components were used.
[0162] Optional ingredient-1: dimethyl silicone oil with a viscosity of 100 mPa·s
[0163] Table 1 Composition of curable silicone composition (Example)
[0164] [Table 1]
[0165]
[0166]
[0167] Table 2 Composition of curable silicone composition (Comparative Example)
[0168] [Table 2]
[0169]
[0170]
[0171] As shown in Examples 1 to 5, the cured product of the present invention has an adhesive strength equivalent to that of glass even for the above-mentioned polarizing plate which is originally difficult to bond or which is prone to have reduced adhesive strength due to curing hindrance. In addition, the cured product shows sufficient shear adhesive elongation as an OCR, and further, the degree of yellowing is small even after being left at a high temperature of 100 degrees for 500 hours.
[0172] On the other hand, in Comparative Examples 1 to 3 where the SiH / Vi ratio of the composition is less than 1, the bonding strength to the polarizer / glass is significantly reduced compared to the bonding strength to the glass / glass. In addition, in Comparative Example 4 that does not contain component (C), the bonding strength to the polarizer is greatly reduced compared to the glass. Furthermore, in Comparative Example 3 where the content of the platinum catalyst is high, the yellowing degree of the cured product after 500 hours at 100 degrees is large, and the optical stability is insufficient as an adhesive for a display device of a display. If the amount of catalyst is increased in order to avoid the problem of poor curing, yellowing occurs, and it cannot be used as a practical adhesive for a display device.
Claims
1. A curable silicone composition, comprising: (A) an organopolysiloxane having at least two alkenyl groups having 2 to 12 carbon atoms in one molecule; (B) the following components (b1) and (b2): (b1) a linear organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain, (b2) an organohydrogenpolysiloxane having at least three silicon-bonded hydrogen atoms in one molecule; (C) one or more selected from (c1) a compound having two or more alkoxysilyl groups in one molecule and (c2) an organic compound having an alkoxysilyl group and an epoxy group in one molecule; and (D) a platinum group metal catalyst activated by light with a wavelength of 200 to 500 nm, in, The content of the component (B) is an amount in which the silicon-bonded hydrogen atoms in the component (B) account for 1 mol or more, relative to 1 mol of the aliphatic unsaturated carbon-carbon bonds in the component (A). The content of platinum atoms in the component (D) is in a range of 15 ppm or less relative to the sum of components that form nonvolatile solid components by the curing reaction of the curable silicone composition.
2. The curable silicone composition according to claim 1, wherein The content of the component (C) is in the range of 0.01 to 5% by mass based on the total amount of the curable silicone composition.
3. The curable silicone composition according to claim 1, wherein The amount of the component (b1) in the component (B) is 60% by mass or more based on the sum of the components (b1) and (b2).
4. The curable silicone composition according to claim 1, wherein The component (A) is one or more selected from the following components (a1) and (a2): (a1) a linear or partially branched organopolysiloxane having at least two alkenyl groups having 2 to 12 carbon atoms in one molecule (a2) From the average unit formula: (R 1 3SiO 1 / 2 ) a (R 1 2SiO 2 / 2 ) b (R 1 SiO 3 / 2 ) c (SiO 4 / 2 ) d (Where R 1 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, R 1 An organopolysiloxane having an alkenyl group, wherein at least 1 mol % is an alkenyl group having 2 to 12 carbon atoms, and a, b, c and d satisfy all of the following conditions: a+b+c+d=1, 0≤a≤0.8, 0≤b≤0.4, 0≤c≤0.8, 0≤d≤0.6, 0.2≤c+d≤0.8).
5. The curable silicone composition according to claim 1, wherein (B) component is the following (b1-1) component and (b2-1) component: (b1-1) a linear organohydrogenpolysiloxane having only silicon-bonded hydrogen atoms at both ends of the molecular chain; (b2-1) According to the average unit formula: (R 2 3SiO 1 / 2 ) e (R 2 2SiO 2 / 2 ) f (R 2 SiO 3 / 2 ) g (SiO 4 / 2 ) h (Where R 2 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms other than an alkenyl group or a hydrogen atom, R 2 At least 1 mol % of which are hydrogen atoms, and e, f, g and h satisfy all of the following conditions: e+f+g+h=1, 0≤e≤0.8, 0≤f≤0.4, 0≤g≤0.7, 0≤h≤0.5, 0.2≤g+h≤0.7).
6. The curable silicone composition according to any one of claims 1 to 5, wherein The viscosity of the composition before ultraviolet irradiation at 25° C. is 100,000 mPa or less.
7. The curable silicone composition according to any one of claims 1 to 6, wherein The curable silicone composition is an optical adhesive or an optical pressure-sensitive adhesive.
8. The curable silicone composition according to claim 1, wherein The amount of silicon atom-bonded hydrogen atoms in the component (B) is 1 mol or more and 4 mol or less per mol of the aliphatic unsaturated carbon-carbon bonds in the component (A). 9 . A cured product, which is the curable silicone composition according to claim 1 .
10. The cured product according to claim 9, wherein The needle penetration at 25°C is in the range of 5 to 70.
11. A laminate, comprising: The adhesive layer is composed of the cured product according to claim 9 and is disposed between a first transparent or opaque optical member and a second transparent or opaque optical member.
12. An optical device, comprising: Base material; an optical element disposed on the substrate; and The cured product according to claim 9, which seals at least a portion of the optical element. 13 . An optical display comprising the laminate according to claim 11 .
Citation Information
Patent Citations
Ultraviolet-curable silicone rubber composition and cured product
JP2019218495A
Curable silicone composition and cured product thereof, layered product and production method therefor, and optical device or optical display
WO2020080348A1